Genetic analysis implicates ERAP1 and HLA as risk factors for severe Puumala virus infection - Haapaniemi, Hele; Strausz, Satu; Tervi, Anniina; Jones, Samuel E; Kanerva, Mari; FinnGen; Estonian Biobank Research Team; Abner, Erik; Fors Connolly, Anne-Marie; Ollila, Hanna M. (OXFORD UNIV PRESS, 2025)
Puumala virus (PUUV) infections can cause severe illnesses such as Hemorrhagic Fever with Renal Syndrome in humans. However, human genetic risk factors contributing to disease severity are still poorly understood. Our goal was to elucidate genetic factors contributing to PUUV infections and understand the biological mechanisms underlying individual vulnerability to PUUV infections. Leveraging data from the FinnGen study, we conducted a genome-wide association study on severe Hemorrhagic Fever with Renal Syndrome caused by PUUV with 2227 cases. We identified associations at the Human Leukocyte Antigen (HLA) locus and ERAP1 with severe PUUV infection. HLA molecules are canonical mediators for immune recognition and response. ERAP1 facilitates immune system recognition and activation by cleaving viral proteins into smaller peptides which are presented to the immune system via HLA class I molecules. Notably, we identified that the lead variant (rs26653, OR = 0.84, P = 2.9 x 10-8) in the ERAP1 gene was a missense variant changing amino acid arginine to proline. From the HLA region, we showed independent and significant associations with both HLA class I and II genes. Furthermore, we showed independent associations with four HLA alleles with severe PUUV infection using conditional HLA fine mapping. The strongest association was found with the HLA-C*07:01 allele (OR = 1.54, P = 4.0 x 10-24) followed by signals at HLA-B*13:02, HLA-DRB1*01:01, and HLA-DRB1*11:01 alleles (P < 5 x 10-8). Our findings suggest an association of viral peptide processing with ERAP1 and antigen presentation through HLA alleles that may contribute to the development of severe PUUV disease.